General profile and job satisfaction of Turkish dietitians - Dağ, Ayhan; Çakır, Biriz; Kılınç, Fatma Nişancı; Türkmen, Evrim Güngör (Progress in Nutrition, 2019)
Objective: The satisfaction is a complex concept involving individual’s experiences and expectations, individual and social values, and job-related attitudes such as motivation and commitment. In this study, it was aimed to evaluate job satisfaction level of dietitians and to determine whether job satisfaction level differs with variables such as working year or work environment. Subject and methods: A questionnaire on demographic characteristics and occupational data, and Job Satisfaction Survey (JSS) were used to determine job satisfaction level. The questionnaire and JSS were sent to 815 dietitians who were member of Turkish Dietetic Association (TDA). The study sample consisted to 227 dietitians. Higher scores in JSS were considered as greater job satisfaction. Data were analyzed by using SPSS for Windows version 16.0. Results: Mean age was 35.3±9.96 years. Of the respondents, 90.3% (n=205) were female; 35.72% had experience of 0-5 years; 18.9% had postgraduate degree; and 5.3% had doctor of philosophy degree. In JSS, mean score was found to be 76.2±10.93 among respondents. When working year and JSS score were compared, highest mean JSS score was found in dietitians with working year≥30 years; followed by those with 21-30 years and those with 0-5 years. The difference between study groups were found to be significant (p<0.05). It was found that JSS cores were comparable between dietitians working or not working in outpatient clinic; however, daily number of patients was associated to job satisfaction level as being lower JSS score by higher patient volume (p<0.05). It was found that there were significant correlations between JSS score and attendance to occupational conference, congress, seminar or training (p<0.05). Higher satisfaction in work environment resulted in higher JSS scores. Conclusions: It was concluded that current problems should be identified and corrected to improve job satisfaction and that are comprehensive studies are needed in this field.